GE_GERICHTE P/448/2016 vom 31. Januar 2017 - GE Cour de justice (2017)
ARME(OBJET) ; LÉSION CORPORELLE SIMPLE ; TENTATIVE(DROIT PÉNAL) ; SÉJOUR ILLÉGAL ; FRAIS JUDICIAIRES | CP22.1 CP123.1.2 LETR115.1.B LARM4.6 CPP135 LSTUP19.A